Orfeu: o arquétipo de um herói atípico - Ribeiro, Prisciane Pinto Fabricio (2017)
The purpose of this work is to analyze the myth of Orpheus taking as a means of transfer the traces of the Greco-Latin literary tradition in order to prove in the immanence of the symbols that surround this myth, the archetypal image of a cultural hero that would have originated, or at least influenced the structuring of the chain of precepts that underlie orphism, a mysterious religion whose doctrines are dissociated from the civic religion of Greece. Noting the diffusion and the scarce literary information about the Orpheus myth, so remote in Greco-Roman culture, the procedures of linguistic-literary analysis applied here comprise the gradual investigation of canonical works that touch, even if minimally, in the figure of Orpheus in order to delimit within this bias the process of development of the hero that culminated in the fulfillment of his mission, his mystical-religious formation, the basis of the Orphic religion.